(untitled) (Research, Society and Development, 2021)
Orthopedic surgeries for stabilizing fractures and joint dislocations are among the three most common surgical procedures in cats. Difficulty in recognizing pain, lack of knowledge regarding the proper use of analgesics and fear of drug side effects can lead to inadequate provision of analgesia in cats. The aim of this research was to describe the main tools for pain assessment and for providing analgesia and anesthesia in orthopedic surgery in cats. This research was developed from the analysis of scientific publications on analgesia and anesthesia in cats, with emphasis on orthopedic surgeries. The UNESP-Botucatu multidimensional pain assessment scale is a powerful and clinically validated tool for post-operative condition of orthopedic surgery in cats. The orthopedic examination can provide significant information about the patient’s general condition. Areas of concern identified on the orthopedic examination are further examined with radiographs or computed tomography. Veterinary medicine has a wide variety of analgesic and anesthetic drugs that can and should be used in felines. However, for the provision of adequate analgesia, knowledge about the metabolic particularities of the feline species is essential, respecting the characteristics of analgesic drugs administered during the pre, trans and post-surgery period, also considering the impact on the choice of doses and routes of management. Appropriate analgesic management, through regular clinical assessment of pain, provides comfort and contributes to the recovery and animal welfare.